1979
DOI: 10.1172/jci109376
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the interaction of purified human erythrocyte AMP deaminase and the human erythrocyte membrane.

Abstract: A B S T R A C T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…However, the interaction with lipids may prove to be physiologically relevant. Whereas hydropathy analysis suggests that AMPD isoforms do not contain putative transmem-brane spanning domains, the AMPD3 enzyme can associate with erythrocyte membrane fractions (40,41). In this report, we provide several independent lines of evidence that the specific, high affinity interaction between the AMPD3 isoform and phosphoinositides constitutes an important mechanism for enzyme regulation and localization.…”
mentioning
confidence: 80%
“…However, the interaction with lipids may prove to be physiologically relevant. Whereas hydropathy analysis suggests that AMPD isoforms do not contain putative transmem-brane spanning domains, the AMPD3 enzyme can associate with erythrocyte membrane fractions (40,41). In this report, we provide several independent lines of evidence that the specific, high affinity interaction between the AMPD3 isoform and phosphoinositides constitutes an important mechanism for enzyme regulation and localization.…”
mentioning
confidence: 80%
“…E1b is one of three identified AMPD3 spliceoforms, and the ⌬M90 variant is modeled after the primary N-terminal proteolytic product generated from this protein during purification and extended storage at 4°C (20). ⌬M90 was typically included in most experiments to simulate proteolyzed endogenous enzyme likely used in a previous study that examined the membrane association of human erythrocyte AMPD (26). Fig.…”
Section: Association Of Ampd3 Enzymes With Erythrocyte Ghosts-mentioning
confidence: 99%
“…Substrate-induced Dissociation of AMPD3 Enzymes from Erythrocyte Ghosts-Previous work has shown that EG association of purified human erythrocyte AMPD results in catalytic inhibition of the enzyme, although substrate concentrations greater than 100 M can disrupt this interaction (26). Therefore, it was necessary to determine a substrate concentration where the EG dissociation of the E1b and ⌬M90 proteins was essentially complete in order that enzyme assay could be used as a reliable quantitative index following their partitioning into EG pellets.…”
Section: Association Of Ampd3 Enzymes With Erythrocyte Ghosts-mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the purified human erythrocyte AMP deaminase binds specifi cally to the cytoplasmic surface of the eryth rocyte membrane and the stability of AMP deaminase is markedly improved by interac tion with the membrane [22], The ability of binding of AMP deaminase to other proteins was also demonstrated [7,21]. Shiraki et al [26] showed that AMP deaminase from rat skeletal muscles binds myosin, and that this binding might modify the regulatory proper ties of AMP deaminase.…”
Section: Distributionmentioning
confidence: 99%